Results of More Than 20,000 Scans with Weightbearing CT - Impact on Costs, Radiation Exposure, and Procedure Time - François Lintz MD, PhD; Martinus Richter MD, PhD (Foot & Ankle Orthopaedics)
Category: Other Introduction/Purpose: Weightbearing CT (WBCT) has been proven to more precisely measure bone position than conventional weightbearing radiographic series (R) and conventional CT (CT). The purpose of this study was to assess the benefit of using WBCT instead of R and/or CT as the standard imaging modality, evaluating image acquisition time, radiation dose, and cost-effectiveness. Methods: All patients who obtained a WBCT as part of standard of care from July 1, 2013 until August 31, 2023 were included in the study. Image acquisition time (T), radiation dose (RD) per patient, and cost-effectiveness were analyzed and compared between the time period using WBCT (yearly average) and the parameters from 2012, i.e. before the availability of WBCT (RCT group). Results: 20,145 WBCT scans were obtained from 9,065 patients (9,056 scans (45%) before treatment; 11,080 scans (55%) at follow-up). On a yearly average, 1,975 WBCTs (bilateral scans) and an additional 11.5 CTs (bilateral feet and ankles) were obtained (WBCT group). In 2012, 1,850 Rs (bilateral feet, dorsoplantar and lateral, metatarsal head skyline view) and 254 CTs were obtained from 885 patients (RCT group). The mean yearly RD was 4.3/4.8uSv for the WBCT/RCT groups (mean difference of 0.5 uSv; a decrease of 10% for the WBCT group; p<.01). Yearly mean T was 115/494 hours in total (3.5/16.0 minutes per patient) for WBCT/RCT groups (mean difference of 379 hours; a 77% decrease for the WBCT group; p<.01). Yearly cost-effectiveness was a mean profit of 55,441/-723 Euro for WBCT/RCT. Conclusion: 20,145 WBCT scans from 9,065 patients over a period of 10.2 years at a foot and ankle department resulted in 10% decreased RD, 77% decreased T, and increased financial profit (65 Euros per patient) for the institution.